2007
DOI: 10.1128/ec.00077-07
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiae Vacuole in Zinc Storage and Intracellular Zinc Distribution

Abstract: Previous studies of the yeast Saccharomyces cerevisiae indicated that the vacuole is a major site of zinc storage in the cell. However, these studies did not address the absolute level of zinc that was stored in the vacuole nor did they examine the abundances of stored zinc in other compartments of the cell. In this report, we describe an analysis of the cellular distribution of zinc by use of both an organellar fractionation method and an electron probe X-ray microanalysis. With these methods, we determined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
123
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(128 citation statements)
references
References 53 publications
3
123
1
1
Order By: Relevance
“…Subcellular location of Mnr2: Studies of the distribution of Mg in yeast cells revealed a predominantly vacuolar location (Simm et al 2007), implicating this All strains were generated during this study except for DY1514 (obtained from David Eide), DBY747, mrs2D-2, and lpe10D-1 (obtained from Anton Graschopf). All strains are isogenic to DY1514 except for those isogenic to DBY747 (lpe10D-1, mrs2D-2, NP103, NP107, and NP112).…”
Section: Resultsmentioning
confidence: 66%
See 4 more Smart Citations
“…Subcellular location of Mnr2: Studies of the distribution of Mg in yeast cells revealed a predominantly vacuolar location (Simm et al 2007), implicating this All strains were generated during this study except for DY1514 (obtained from David Eide), DBY747, mrs2D-2, and lpe10D-1 (obtained from Anton Graschopf). All strains are isogenic to DY1514 except for those isogenic to DBY747 (lpe10D-1, mrs2D-2, NP103, NP107, and NP112).…”
Section: Resultsmentioning
confidence: 66%
“…In part, this model proposes that, in Mg-replete conditions, an intracellular compartment (most probably the vacuole) provides a storage site for excess Mg. Consistent with this idea, the vacuolar Mg concentration is approximately fourfold higher than the cytoplasmic concentration in Mg-replete yeast cells (Simm et al 2007). The accumulation of excess Mg in the vacuole would require active transport to overcome the charge gradient generated by V-ATPase activity.…”
Section: Model For Mnr2 Function In Yeastmentioning
confidence: 68%
See 3 more Smart Citations